Em minoria : uma análise da relação entre as oposições e o governo Olívio Dutra no Rio Grande do Sul (1999-2002) - Lapuente, Rafael Saraiva (2020)
This paper analyzes how parliamentary disputes between situational deputies and opponents during the Olívio Dutra government in Rio Grande do Sul (1999-2002), helping to understand how they legitimize their positions in the field of symbolic disputes. For this, it is used as a source of speeches by deputies in the Legislative Assembly of Rio Grande do Sul, in addition to anchoring in newspapers of the period (Correio do Povo and Zero Hora). To make this analysis, support in French sociology Pierre Bourdieu and his disciples, to understand how symbolic struggles between agents in the political field and how to seek to legitimize them in the social world, believing and making them believe that they spoke and acted in the name of people. Thus, it was possible to understand the way in which a parliamentary opposition, which was largely a majority in the Legislative Assembly, sought to build as a representative of public opinion as opposed to the Rio Grande do Sul executive in themes used for the status of Olívio Dutra in the arena of symbolic disputes in the regional political field.